Reduction in nitrogen dioxide concentration by soda lime preparations during simulated nitric oxide inhalation - Weimann, Jörg; Hagenah, Jens-Uwe; Motsch, Johann (British journal of anaesthesia, 1997)
Nitrogen dioxide is formed during delivery of inhaled nitric oxide for the treatment of patients with pulmonary hypertension. Soda lime has been shown to absorb nitrogen dioxide. We tested three different commercially available soda lime preparations (Sodasorb, Drägersorb 800 and Sofnolime) for their efficacy in absorbing nitrogen dioxide and nitric oxide during simulated nitric oxide inhalation. All soda lime preparation absorbed nitrogen dioxide (15%, 24% and 34%, respectively). To test if this difference could be attributed to the potassium hydroxide (KOH) content of the different preparations, two other preparations with a higher (3.0% and 7.3% w/w, respectively) KOH content were tested and we found an increase in nitrogen dioxide removal up to 47% and 46%, respectively. We conclude that soda lime absorbed nitrogen dioxide during nitric oxide inhalation. This effect seemed to be moderate under simulated clinical conditions, but increased using soda lime with a higher KOH content. Nevertheless, we recommend continuous monitoring of inspired nitrogen dioxide concentration during clinical inhalation of nitric oxide.